2015
DOI: 10.1097/ico.0000000000000496
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Allergen-Specific IgE Serum Levels in Patients With Ocular Allergy

Abstract: Perennial allergic conjunctivitis was the most prevalent disorder and demonstrated higher positivity in class V/VI for specific antigens (mixed dust mites, dp, and df), indicating high antigenicity. Dust mites, D. pteronyssinus, D. farinae, B. germanica, and B. tropicalis were the primary triggers of the studied ocular allergies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
4
2
Order By: Relevance
“…Hence, the matched control groups in studies evaluated in our review may not reflect a non-selected background population, but rather reflect that groups constituted by individuals selected based on history or symptoms of any allergy or allergy-associated diseases. For comparison, the prevalence of a positive allergy test in patients with seasonal allergic conjunctivitis is reported in the range of ~60%-70% (Almaliotis et al, 2013;Jongvanitpak et al, 2020;Polido et al, 2015), which is slightly higher than that we find in patients with VKC.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…Hence, the matched control groups in studies evaluated in our review may not reflect a non-selected background population, but rather reflect that groups constituted by individuals selected based on history or symptoms of any allergy or allergy-associated diseases. For comparison, the prevalence of a positive allergy test in patients with seasonal allergic conjunctivitis is reported in the range of ~60%-70% (Almaliotis et al, 2013;Jongvanitpak et al, 2020;Polido et al, 2015), which is slightly higher than that we find in patients with VKC.…”
Section: Discussioncontrasting
confidence: 82%
“…The 33 studies included in our review summarized data on a total of 2122 patients with VKC. Studies were predominantly based on patients from ophthalmology clinics, and in seven studies patients were recruited from allergology clinics or paediatric clinics (Gómez‐Henao et al, 2018 ; Jongvanitpak et al, 2020 ; Kocaturk et al, 2012 ; Monzón et al, 2009 ; Polido et al, 2015 ; Tesse et al, 2010 ; Zicari et al, 2013 ). Studies were based on populations in Asia ( n = 14), Europe ( n = 14), South America ( n = 3), and Africa ( n = 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, there was not found a significant difference between AR patients with allergic conjunctivitis than those without conjunctivitis for the mean IgE levels (p=0.269). In some of the previous studies, it was observed that its levels might increase in ocular allergy compared to the healthy controls (9,11,20). In addition, when patients with high IgE levels were evaluated, no significant difference was found in terms of the frequency of concomitant conjunctivitis in this study (55.3% vs. 50.8%, respectively, p=0.634).…”
Section: Discussioncontrasting
confidence: 56%